Climate and livestock policy coherence analysis in Kenya, Ethiopia and Uganda - Ashley, Laurie (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2019)
Livestock in Kenya, Ethiopia, and Uganda play an important role in food security, livelihoods, income, and gross domestic product (GDP). Livestock sector growth in response to growing demand for animal-sourced food requires policy guidance to avoid increasing livestock sector exposure to climate risks and increasing sector greenhouse gas (GHG) emissions. Guided by the Policy Coherence for Sustainable Development Framework, this analysis examines 40 climate, agriculture, livestock, development, land, and environment policies across the three countries for strength and coherence in addressing livestock sector adaptation and mitigation. The policy context is dynamic with numerous policies developed since 2015 particularly in the climate and development policy areas but also for livestock, agriculture, and land. Countries are clearly working to integrate livestock climate change strategies into climate and other policy areas, although at times with limited detail and coherence. More recent policies often provide the most comprehensive approaches and detailed strategies and post-2015 policies are largely aligned with the SDGs with some exceptions. Development partners, including bilateral, multilateral, research, and private sector organizations often play key roles in technical and financial support for policy development related to livestock sector adaptation and mitigation.